The Relationship Between Acces to Health Services and Medication Control Compliance of Patients with Schizophrenia - Maryati Agustina Barimbing; Fepyani Thresna Feoh; Franto Yusup Maromon (NHM PRESS, 2021)
Schizophrenia is a neurological disorder that influence perception, way of thinking, language, emotional and social behavior. Treatment should be sustainable to prevent relapse, so patient can be productive in daily life. One of the things that important in medication control compliance of patient with schizophrenia is access to health services. The aim of this study want to know the relationship between access to health services with medication control compliance of patient with schizophrenia in Poli Jiwa Rumah Sakit Jiwa (RSJ) Naimata Kupang. This study is quantitative study with correlation analityc design and cross sectional approach. The sample of this study is 75 family member of patient with schizophrenia were selected by purposive sampling. Data collection using questionare and observation sheet. The result of this study showed ρ value=0,000 with OR=8,643. It can be concluyded that there is relationship between access to health services with medication control compliance of patient with schizophrenia in Poli Jiwa Rumah Sakit Jiwa (RSJ) Naimata Kupang. Keywords: Access, Medication control compliance, Schizophrenia